Long‐term exercise in mice has sex‐dependent benefits on body composition and metabolism during aging. Issue 21 (14th November 2016) - McMullan, Rachel C.; Kelly, Scott A.; Hua, Kunjie; Buckley, Brian K.; Faber, James E.; Pardo‐Manuel de Villena, Fernando; Pomp, Daniel
Abstract: Aging is associated with declining exercise and unhealthy changes in body composition. Exercise ameliorates certain adverse age‐related physiological changes and protects against many chronic diseases. Despite these benefits, willingness to exercise and physiological responses to exercise vary widely, and long‐term exercise and its benefits are difficult and costly to measure in humans. Furthermore, physiological effects of aging in humans are confounded with changes in lifestyle and environment. We used C57BL/6J mice to examine long‐term patterns of exercise during aging and its physiological effects in a well‐controlled environment. One‐year‐old male ( n  = 30) and female ( n  = 30) mice were divided into equal size cohorts and aged for an additional year. One cohort was given access to voluntary running wheels while another was denied exercise other than home cage movement. Body mass, composition, and metabolic traits were measured before, throughout, and after 1 year of treatment. Long‐term exercise significantly prevented gains in body mass and body fat, while preventing loss of lean mass. We observed sex‐dependent differences in body mass and composition trajectories during aging. Wheel running (distance, speed, duration) was greater in females than males and declined with age. We conclude that long‐term exercise may serve as a preventive measure against age‐related weight gain and body composition changes, and that mouse inbred strains can be used to characterize effects of long‐term exercise and factors (e.g. sex, age) modulating these effects. These findings will facilitate studies on relationships between exercise and health in aging populations, including genetic predisposition and genotype‐by‐environment interactions. Abstract : This study demonstrates that exercise prevents doubling of body fat, significant gains in body mass, and loss of lean mass during aging. It also provides evidence of the effect of sex on exercise, body mass, and body composition trajectories during aging. Thus, this study demonstrates that long‐term exercise (starting in midlife) may be used as a preventive measure against age‐related weight gain and changes in body composition.